The Construction of Self-Identity in the Chronically Mentally Ill: A Focus on Autobiographic Narratives of Mentally Ill Patients in South Korea - Nam, Sang-hui (Qualitative Sociology Review, 2008)
A systematic policy for treatment and management of chronic psychiatric patients in South Korea was begun with the passage of the Mental Health Act in 1995. The mentally ill patients who were previously separated from the society now have opportunities to live in local communities under medication with the help of rehabilitation facilities. This study aims to understand how mentally ill patients deal with their new medical environment. An autobiographic narrative analysis is methodically applied in order to link the social and the individual levels. Autobiographic narratives of illness show how the patient’s self-identity is formed and further developed according to the chronic conditions of his illness and the continual learning from experiences. In regard to the construction of selfidentity, two aspects should be taken into consideration: First, medication is absolutely necessary before patients can leave the hospital and participate in rehabilitation programs. Secondly, social integration is usually evaluated by the return of the patient into a normal biographical stage. It turns out that medication deprives the patients of control over their emotions, their bodies. Furthermore, their social environments – including family, friends and the labor market – work against them. Under these circumstances, mentally ill patients are liable to adhere to their own interpretation of mental illness, and what they experience is far different from the expectations of experts in the field. The new mental health environment also contributes to the formation of patient communities. As a result, chronic psychiatric patients are able to build their own subculture and to see themselves through their own eyes. Further studies are needed to explore whether and to what extent the ongoing improvement of social conditions for mentally ill patients has an impact on autobiographic narratives and self-identity construction.